Last Glacial Maximum sea surface temperature and sea-ice extent in the Pacific sector of the Southern Ocean - Verena Benz; Oliver Esper; Rainer Gersonde; Frank Lamy; Ralf Tiedemann (Quaternary Science Reviews, 2016)
Abstract Sea surface temperatures and sea-ice extent are most critical variables to evaluate the Southern Ocean paleoceanographic evolution in relation to the development of the global carbon cycle, atmospheric \{CO2\} and ocean-atmosphere circulation. Here we present diatom transfer function-based summer sea surface temperature (SSST) and winter sea-ice (WSI) estimates from the Pacific sector of the Southern Ocean to bridge a gap in information that has to date hampered a well-established reconstruction of the last glacial Southern Ocean at circum-Antarctic scale. We studied the Last Glacial Maximum (LGM) at the \{EPILOG\} time slice (19,000–23,000 calendar years before present) in 17 cores and consolidated our \{LGM\} picture of the Pacific sector taking into account published data from its warmer regions. Our data display a distinct east-west differentiation with a rather stable \{WSI\} edge north of the Pacific-Antarctic Ridge in the Ross Sea sector and a more variable \{WSI\} extent over the Amundsen Abyssal Plain. The zone of maximum cooling (>4 K) during the \{LGM\} is in the present Subantarctic Zone and bounded to its south by the 4 °C isotherm. The isotherm is in the \{SSST\} range prevailing at the modern Antarctic Polar Front, representing a circum-Antarctic feature, and marks the northern edge of the glacial Antarctic Circumpolar Current (ACC). The northward deflection of colder than modern surface waters along the South American continent led to a significant cooling of the glacial Humboldt Current surface waters (4–8 K), which affected the temperature regimes as far north as tropical latitudes. The glacial reduction of \{ACC\} temperatures may also have resulted in significant cooling in the Atlantic and Indian Southern Ocean, thus enhancing thermal differentiation of the Southern Ocean and Antarctic continental cooling. The comparison with numerical temperature and sea-ice simulations yields discrepancies, especially concerning the estimates of the sea-ice fields, but some simulations reproduce well our proxy-based temperature data.
Keywords: Pacific Southern Ocean